Workload, job, and family satisfaction in dual-earning parents with adolescents: the mediating role of work-to-family conflict - Schnettler, Berta; Concha-Salgado, Andrés; Orellana, Ligia; Saracostti, Mahia; Beroiza, Katherine; Poblete, Héctor; Lobos, Germán; Adasme-Berríos, Cristian; Lapo, María; Riquelme-Segura, Leonor; Sepúlveda, José A.; Reutter, Karol; et al. (Frontiers in Psychology, 2025)
IntroductionThe study examined the direct and indirect effects of parents’ workload, work-to-family conflict (WtoFC), job satisfaction, and family satisfaction among dual-earning parents and their adolescent children.MethodsA total of 516 dual-earning parents and one adolescent child were enlisted for the study using non-probabilistic sampling. Mothers and fathers completed assessments about workload, WtoFC, and the Overall Job Satisfaction Scale, while all three family members responded to the Satisfaction with Family Life Scale.ResultsThe data were analyzed using the mediation Actor-Partner Interdependence Model and structural equation modeling. The findings revealed a negative association between mothers’ workload and family satisfaction. Moreover, both parents’ workloads reduce adolescents’ family satisfaction. Both parents’ workload was positively associated with their WtoFC. Additionally, WtoFC was found to significantly mediate across intraindividual and interindividual domains, linking workload and job satisfaction in parents and workload and family satisfaction for parents and their adolescent children.DiscussionThese empirical insights underscore the critical need to mitigate workload and WtoFC to enhance parental job satisfaction and family satisfaction of all family members. The study’s practical implications provide the audience with actionable insights that can be applied to workplace practices, empowering them to make informed decisions.